Materials structure and heat and mass transfer : special topic volume with invited peer-reviewed papers only - Zidani, Mosbah; Farh, Hichem (Diffusion and defect data. Defect and diffusion forum, 2021)
This volume contains articles reflected the last results in numerical simulation of transfer phenomena in heat and fluid flow in the various technical systems and also includes descriptions of engineering decisions for the improvement of effective using renewable energy. The presented issue will be useful for a wide range of engineers and researchers from many branches of engineering science. Heat Transfer, Mass Transfer, Fluid Flow, Fluid Dynamics, Convection Flow, Mixed Convection, Turbulent Flow, Ventilation, Cooling, Drying Kinetics, Absorption, Numerical Modelling, Renewable Energy, Solar Cells, Fuel Cells, Non-Premixed Combustion, Energy Systems Engineering, Convertor, Micro Grid Materials Science, Mechanical Engineering, Manufacturing.